Tathwir Maddah al-Imla’ ‘ala Asas Namudzaj al-Ta’allum al-Madmaj li Thalabah Jami’ah - Pimada, Luluk Humairo; Rasyidi, Abdul Wahab (Institut Agama Islam Negeri Curup, 2023)
This research aimed to develop imla' materials for non-Arabic learners based on blended learning through learning technology media, to answer the challenges of technological development alongside current trends and to meet students' needs regarding digitalization development. This research was development research using the ASSURE model with 6 stages, namely analyzing students, stating performance goals, selecting methods, media and materials, utilizing media and materials, requiring students’ participation, evaluating and revising. The levels of effectiveness and significance were acquired from trials on all third semester Arabic language education students, experts, and teachers (imla' materials) using the T test formula, accompanied by instruments in the form of questionnaires, pre-tests, and post-tests. The results of this research were a set of printed teaching materials in the form of modules that could be accessed through technology-based learning media to meet students' needs regarding development in the current world of digitalization. The significance of this development could be seen based on the results of evaluating students' abilities during learning with a total score of 1.66 %, and the significant value was 0.05. The development of imla' material was declared effective and efficient.